2009
DOI: 10.1021/jp901234z
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Intramolecular Hydrogen Atom Transfer and Solvation Dynamics of the Medicinal Pigment Curcumin

Abstract: The potential use of the naturally occurring yellow-orange pigment curcumin as a photodynamic therapy agent is one of the most exciting applications of this medicinal compound. Although subnanosecond spectroscopy has been used to investigate the photophysical processes of curcumin, the time resolution is insufficient to detect important and faster photoinduced processes, including solvation and excited-state intramolecular hydrogen atom transfer (ESIHT). In this study, the excited-state photophysics of curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
152
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(163 citation statements)
references
References 49 publications
10
152
1
Order By: Relevance
“…23 Additionally, the ESIHT time constant of curcumin reported in this study is comparable to that of 7-azaindole in methanol. 49 The good agreement indicates a substantial level of curcumin-solvent and curcumin-surfactant intermolecular hydrogen bonding in the micelle.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellessupporting
confidence: 59%
See 3 more Smart Citations
“…23 Additionally, the ESIHT time constant of curcumin reported in this study is comparable to that of 7-azaindole in methanol. 49 The good agreement indicates a substantial level of curcumin-solvent and curcumin-surfactant intermolecular hydrogen bonding in the micelle.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellessupporting
confidence: 59%
“…22 The ESIHT time constant of curcumin in this nonpolar solvent is shorter than that in methanol, which has a value of ∼70 ps. 23 The results imply that the strength of the intramolecular hydrogen bond of curcumin is the determining factor in the rate of ESIHT. These authors, furthermore, suggest that in protic solvents, such as methanol and ethanol, the keto-enol group of curcumin forms strong hydrogen bonds with the solvent molecules, in addition to the intramolecular hydrogen bond within the keto-enol group.…”
Section: Uv-vis Absorption and Emission Spectra Of Curcumin In Micellesmentioning
confidence: 92%
See 2 more Smart Citations
“…11,18,19 Recently, Adhikary et al studied the excited state photophysics of curcumin in protic solvent and surfactant micelles by using femtosecond fluorescence upconversion spectroscopy. 20 They found that one of the decay time constants, i.e., the longer one, changed significantly when the enolic hydrogen of curcumin was deuterated. It was thus assigned to the ESIHT process, whereas the shorter time constant that did not change was thought to be associated with the process of solvation.…”
Section: Introductionmentioning
confidence: 99%